2020
DOI: 10.3389/fsufs.2020.510982
|View full text |Cite
|
Sign up to set email alerts
|

Biochar as Influenced by Feedstock Variability: Implications and Opportunities for Phosphorus Management

Abstract: Agricultural wastes from plant and animal operations are often land applied to recycle and manage residues. Compositional variability among these wastes is vast. Some waste components can potentially represent a threat to the environment and humans depending on their nature, application loads, and soil type. Biochar, the product obtained by biomass heating under oxygen-limited conditions, has the potential to minimize risks associated with waste characteristics while promoting soil health. However, variation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Compared to different types of biochars, bonechar had high total P, while the plant available P (M3-P) in the bonechar, was higher (2,800 mg kg -1 ) than plant-based biochars with M3-P <480 mg kg -1 , although lower than animal-based biochars (>7,000 mg kg -1 ). 9 The high M3-P concentrations in the bonechar suggests that the material could be a good P fertilizer source. Warren et al 8 indicated that the bonechar P solubility was intermediate between Gafsa phosphate rock and triple superphosphate fertilizer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to different types of biochars, bonechar had high total P, while the plant available P (M3-P) in the bonechar, was higher (2,800 mg kg -1 ) than plant-based biochars with M3-P <480 mg kg -1 , although lower than animal-based biochars (>7,000 mg kg -1 ). 9 The high M3-P concentrations in the bonechar suggests that the material could be a good P fertilizer source. Warren et al 8 indicated that the bonechar P solubility was intermediate between Gafsa phosphate rock and triple superphosphate fertilizer.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical analyses included total P and Mehlich 3 (M3)-extractable K, Ca, Mg, Zn, Si, Na, Mn, Cu, Fe, Al, B, Cd, Ni and Pb. Details of the methodology are available in Freitas et al 9…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, investigating nutrients dynamic (both leaching and adsorption) by agricultural soils amended with animal-biomasses-derived-biochars is a crucial task in order to get a better appreciation of their possible impacts onto soils, water resources, and plants' growth [8]. Nutrients dynamic in biochars-amended-soils have been investigated under controlled laboratory conditions in batch, column, and pots devices and also in field trials [5,[14][15][16]. Results indicated that nutrients dynamic is a very complex process that depends on various parameters such as the physicochemical properties of the nutrient, the biochar, and the agricultural soil as well as the used experimental conditions giving the impression that outcomes of different studies look like contradictory [6,12,14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients dynamic in biochars-amended-soils have been investigated under controlled laboratory conditions in batch, column, and pots devices and also in field trials [5,[14][15][16]. Results indicated that nutrients dynamic is a very complex process that depends on various parameters such as the physicochemical properties of the nutrient, the biochar, and the agricultural soil as well as the used experimental conditions giving the impression that outcomes of different studies look like contradictory [6,12,14,16,17]. For instance, Zolfi-Bavariani et al [6] and Hadroug et al [17] showed that more alkaline biochars, that are produced at higher pyrolysis temperatures, released higher rates of potassium.…”
Section: Introductionmentioning
confidence: 99%